2012
DOI: 10.5624/isd.2012.42.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Optimal protocol for teleconsultation with a cellular phone for dentoalveolar trauma: an in-vitro study

Abstract: PurposeDental trauma is frequently unpredictable. The initial assessment and urgent treatment are essential for dentists to save the patient's teeth. Mobile-phone-assisted teleconsultation and telediagnosis for dental trauma could be an aid when a dentist is not available. In the present in-vitro study, we evaluated the success rate and time to transfer images under various conditions.Materials and MethodsWe analyzed the image quality of cameras built into mobile phones based on their resolution, autofocus, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…The frontal view included the maxillary anterior region, capturing the canines, lateral and central incisors, and areas of free and attached gingiva. The occlusal view registered the same teeth from an occlusal perspective, reaching up to the anterior region of the palate, according to the protocol suggested by Park et al . The third photograph was taken with the teeth in occlusion (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frontal view included the maxillary anterior region, capturing the canines, lateral and central incisors, and areas of free and attached gingiva. The occlusal view registered the same teeth from an occlusal perspective, reaching up to the anterior region of the palate, according to the protocol suggested by Park et al . The third photograph was taken with the teeth in occlusion (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…In such contexts, the use of teledentistry (TD) can mitigate the limitations of the traditional management of TDIs . TD is defined as remote dental assistance—that is, without direct contact with the patient—and it is used for diagnosis and in support systems for clinical decisions .…”
Section: Introductionmentioning
confidence: 99%
“…The functions of smartphone cameras (autofocus, anti-movement, and white-balance) permit fine detail and color visualization in dental images. [19] Transmitting these images appended with patients’ symptoms to a dentist could improve patient-provider communication in real-time and enable dentists to make more timely treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, dental mobile applications have included various functions such as data collection, [21] symptom checking, [22] and photographing and transmitting high-quality dental images. [19,23] Additionally, Namakian [24] has shown that dentists can assess patients remotely, as well as in person if accurate information is available. Therefore, with proper information captured remotely, clinical decision-making such as treatment plans and resource allocations could be supported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, teleradiology systems have been widely used in the medical field and even studies of remote interpretation via a mobile hand held device have been reported 2-4. However, little research has addressed the application of teleradiology to dentistry, and most such studies are limited to investigation of specific diseases such as maxillofacial pathoses requiring surgery or temporomandibular joint (TMJ) disorder 5-8.…”
Section: Introductionmentioning
confidence: 99%